Understanding Digital Humanities
XVIII, 318 p.
Keywords: Confronting the digital revolution in academia, this book examines the application of new computational techniques and visualisation technologies in the Arts & Humanities. Uniting differing perspectives, leading and emerging scholars discuss the theoretical and practical challenges that computation raises for these disciplines.